A component method model for blind-bolts with headed anchors in tension - Pitrakkos, Theodoros; Tizani, Walid (Techno Press, 2015)
The successful application of the component-based approach – widely used to model structural joints – requires knowledge of the mechanical properties of the constitutive joint components, including an appropriate assembly procedure to derive the joint properties. This paper presents a component-method model for a structural joint component that is located in the tension zone of blind-bolted connections to concrete-filled tubular steel profiles. The model relates to the response of blind-bolts with headed anchors under monotonic loading, and the blind-bolt is termed the "Extended Hollo-bolt". Experimental data is used to develop the model, with the data being collected in a manner such that constitutive models were characterised for the principal elements which contribute to the global deformability of the connector. The model, based on a system of spring elements, incorporates pre-load and deformation from various parts of the blind-bolt: (i) the internal bolt elongation, (ii) the connector’s expanding sleeves element, and (iii) the connector’s mechanical anchorage element. The characteristics of these elements are determined on the basis of piecewise functions, accounting for basic geometrical and mechanical properties such as the strength of the concrete applied to the tube, the connection clamping length, and the size and class of the blind- bolt’s internal bolt. An assembly process is then detailed to establish the model for the elastic and inelastic behaviour of the component. Comparisons of model predictions with experimental data show that the proposed model can predict with sufficient accuracy the response of the component. The model furthers the development of a full and detailed design method for an original connection technology.